ANALISIS KESESUAIAN GERAKAN PEMANASAN KHUSUS DENGAN LATIHAN GERAKAN INTI PADA PENCAK SILAT - Andy, Florensius; Samodra, Y. Touvan Juni; Gandasari, Maharani Fatima (Universitas Tanjungpura, 2025)
Proper warm-up is very important to prevent injury and improve the performance of martial artists. The suitability of special warm-up with core training in pencak silat is something that coaches need to pay attention to in coaching martial artists. Warm-up is an activity before starting training in various sports. The training load from the warm-up session, core training, and closing must be given according to the characteristics and needs of each martial artist. This study aims to assess the suitability of special warm-up movements for pencak silat martial artists to perform movements related to core movement. training. The research sample from the Kijang Berantai Pontianak school with a total of 15 people. The research instruments were observation sheets and documentation. The data analysis technique used was descriptive quantitative. The results of the analysis can be concluded that on the first day of core punch training there were 17 Special Warm-ups that were suitable for core training with a total percentage of 42.5%. On the second day of core training for front kicks, crescent kicks, T kicks there were 24 Special Warm-ups that were suitable with a total percentage of 60%. On the third day of core training for scissors and blocks there were 15 Special Warm-ups that were suitable on the third day with a percentage of 37.5%. So from the overall research results, the specific warm-up is still not suitable for the core training. Suggestions for trainers to practice and pay attention to the ability to be adjusted to the core training warm-up until the end so that the training undertaken does not trigger the risk of injury and can optimize the performance of the athletes.